EFL Pre-Service Teachers’ Perspectives on Digital Reading Instruction for Young Learners - Raisa Fadilla; Fahmi Hidayat; Emma Rosana Febriyanti (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
Recent technology advancements have altered the perception of literacy, and it is no longer limited to the connection with the print text. The shifting meaning of literacy has been reflected in the growing number of teachers who are integrating digital learning into their reading instruction. However, little is known about the evidence of future teachers’ views on the implementation of digital learning, specifically in relation to young learners’ early literacy. Thus, this study aims to examine pre-service teachers’ perceptions of the benefits, drawbacks, and reading skills taught by using digital learning to enhance early reading skills in EFL context. This study will investigate seventy pre-service teachers who have taken English for Young Learners courses. The data of this study is collected by distributing questionnaires consisting of three aspects (benefits, drawbacks, and reading skills) concerning digital learning usage, using a Likert scale (strongly disagree, disagree, agree, and strongly agree) as the measurement. The survey will be conducted using google form. The study's findings will reveal how pre-service teachers perceive the benefits, drawbacks, and reading skills taught by implementing digital learning in young learners’ classrooms. Keywords: digital reading, young learners, english, pre-service teachers, teachers’ perception